How can I demonstrate that (sin(T)+cos(T))(1-sin(T)cos(T))=(sin(T))^3+(cos(T))^3

You first develop the expression on the left side of the equation:(sin(T)+cos(T))(1-sin(T)cos(T))=sin(T)-sin^2(T)cos(T)+cos(T)-sin(T)cos^2(T)=sin(T)(1-cos^2(T))+cos(T)(1-sin^2(T))Now, you will need to use the formula cos^2(T)+sin^2(T)=1Hence, 1-cos^2(T)=sin^2(T) and 1-sin^2(T)=cos^2(T)You now have the following equation: (sin(T)+cos(T))(1-sin(T)cos(T))=sin(T)(sin^2(T))+cos(T)(cos^2(T))QED

Answered by Tabea C. Maths tutor

2666 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What does differentiation actually mean?


What are the limits of an inverse tan graph.


How do I show two lines are skew?


Given (x-2) is a factor of ax^3 + ax^2 + ax - 42, find the value of a


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences